148 Management of Unruptured Intracranial Aneurysms in the Elderly: A Cost-Effectiveness Analysis. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Wu, Xiao; Cord, Branden J; Sommaruga, Samuel A C; Matouk, Charles C; Malhotra, Ajayy
Abstract: INTRODUCTION: Unruptured intracranial aneurysms (UIAs) are relatively common, with a significant proportion in patients above 65 yr of age. This study evaluates the cost-effectiveness of 5 different management strategies for UIAs in elderly patients—annual magnetic resonance angiography (MRA) screening, biennial MRA screening, MRA screening every 5 yr, coiling and follow-up and, no treatment or preventive follow-up. METHODS: A decision-analytic model-based cost-effectiveness analysis was done using inputs from the medical literature. A Markov decision model was constructed from a societal perspective starting with patients 65-yr-old on average, with incidental detections of UIA and no prior history of subarachnoid hemorrhage. Probabilistic, 1-way, and 2-way sensitivity analyses were performed. RESULTS: The base-case calculation shows no preventive follow-up to be the most cost-effective strategy (cost: 10 838, health benefit: 14.01 quality-adjusted life years), showing lower costs and higher effectiveness. Among the imaging follow-ups, MRA every 5 yr is the most cost-effective. The conclusion remains robust in probabilistic and 1-way sensitivity analyses. No routine follow-up remains the optimal strategy when the annual growth rate and rupture risk of growing aneurysms are varied. When the annual rupture risk of nongrowing UIAs is 5.3%, coiling should be performed directly. CONCLUSION: Given the current literature, routine preventive treatment or periodic, close imaging follow-up is not a cost-effective strategy in all elderly patients with UIAs. More aggressive management strategies might be more appropriate in selected patients at high risk for rupture.